2016
DOI: 10.1111/sms.12674
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic fitness on cerebral blood flow and cerebral vascular responsiveness to CO2 in young and older men

Abstract: We sought to test the hypothesis that brain blood flow and cerebral vascular responsiveness to carbon dioxide (CVR ) are greater in aerobically trained young and old individuals compared to their untrained counterparts. In 11 young trained {[23 (20-26) years] [mean (95% confidence interval)]}, 10 young untrained [25 (22-28) years], 8 older trained [65 (61-69) years], and 9 older untrained [67 (64-71) years] healthy individuals, Doppler ultrasound of the internal carotid (ICA) and vertebral (VA) artery blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 54 publications
2
37
2
1
Order By: Relevance
“…For instance, aerobic exercise training alters favorably cerebrovascular health in varying clinical conditions ranging from chronic obstructive pulmonary disease (Lewis et al, ), cognitive impairments (Alfini et al, ), stroke (Ivey et al, ) and following cancer (Northey et al, ). Evidence show that life‐long aerobic training individuals with elevated CRF have higher resting intracranial blood velocity in the anterior circulation (as indexed by transcranial Doppler sonography of mean blood velocity in middle cerebral artery (MCAv mean ) (Ainslie et al, ; Bailey et al, ), and in the posterior circulation (as indexed by arterial spin labeling in posterior cingular cortex/precuneus) (Thomas et al, ) and higher extracranial blood flow (as indexed by carotid Doppler) (Braz et al, ) than their sedentary counterparts. In inactive individuals, short‐term aerobic training (12 weeks) longitudinally elevates CRF and cerebrovascular reactivity to carbon dioxide, whereas it induces equivocal MCAv mean responses at rest (Murrell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, aerobic exercise training alters favorably cerebrovascular health in varying clinical conditions ranging from chronic obstructive pulmonary disease (Lewis et al, ), cognitive impairments (Alfini et al, ), stroke (Ivey et al, ) and following cancer (Northey et al, ). Evidence show that life‐long aerobic training individuals with elevated CRF have higher resting intracranial blood velocity in the anterior circulation (as indexed by transcranial Doppler sonography of mean blood velocity in middle cerebral artery (MCAv mean ) (Ainslie et al, ; Bailey et al, ), and in the posterior circulation (as indexed by arterial spin labeling in posterior cingular cortex/precuneus) (Thomas et al, ) and higher extracranial blood flow (as indexed by carotid Doppler) (Braz et al, ) than their sedentary counterparts. In inactive individuals, short‐term aerobic training (12 weeks) longitudinally elevates CRF and cerebrovascular reactivity to carbon dioxide, whereas it induces equivocal MCAv mean responses at rest (Murrell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Thomas et al study, Master athletes were found to have a significantly reduced BOLD CVR compared to their sedentary counterparts over most of cerebral cortex. While most studies into these effects have identified a positive relationship between CVR and fitness [35][36][37][38] , these studies used transcranial Doppler (TCD) to measure effects.…”
Section: Discussionmentioning
confidence: 99%
“…If CVR is taken to be a marker of vascular health, it can be posited that those with higher fitness levels would have greater CVR, as their vascular system would be more compliant and have an increased ability to respond to a vasodilatory stimulus. Yet, the literature has found conflicting results, where some have observed increased CVR in relation to higher fitness levels [35][36][37][38] , others have found decreased CVR is related to increased fitness 19 , while others have found no difference [39][40][41] in aging. It is unclear however if this is due to differences in measurement method, spatial localization of the measurement or an interesting physiological interplay between multiple hemodynamic aspects of brain health.…”
Section: Introductionmentioning
confidence: 99%
“…99 In the cerebral circulation, there is conflicting evidence regarding the role of cardiorespiratory fitness. Some studies report that endurance-trained individuals have greater cerebrovascular reactivity 100 or no differences in cerebrovascular reactivity 101 or that cerebrovascular reactivity is positively associated with VO 2 max. 102,103 In addition, trained men have greater MCA blood velocity throughout the life span compared to sedentary men.…”
Section: And Cardiorespiratory Fitnessmentioning
confidence: 99%